Appreciation in Kiamat Dance Performance in Kuripan Village South Lampung (Catharsis, 2022)
Art and society are two inseparable things that go hand in hand and influence each other. It shows that the existence of a work of art cannot be separated from public appreciation. Society has contributed as a mover, changer, maintenance, and creator of the artwork presence. This study has examined the community's appreciation of a performance of the Kiamat Dance (Doomsday Dance), a heritage dance from the Keratuan Darah Putih in Kuripan Village, South Lampung Regency. The research used descriptive qualitative methods with a case study design (real-life events). Data collection used observation, interviews, and documentation. The validity technique used triangulation of data sources. Analysis of the data used an analytical approach by Janet adshead et al., which divides the dance analysis into four stages: describing, interpreting, and evaluating. The study results show that the Kiamat Dance is one of the dances contained in the traditional ruwah procession or the wedding celebration of the king of the Keratuan Darah Putih. It is called the Kiamat Dance because it is performed at the end of a ruwah event or as a closing dance. Descendants from the kingdom dance, but the musicians are residents, as stated by Osborn. He has divided appreciation into two parts: appreciation as an attitude which refers to habits and expertise, and appreciation as an action. The Kiamat Dance performance in the traditional ruwah procession is a stimulus-response practice. There is a stimulus from the feeling of belonging and the need to carry out the dance performance in a traditional ruwah procession, reproducing a repetitive activity, thus forming a habit. These stimulus-response activities then start actions in the form of respect, ownership, and direct involvement of the community in activities, which are unconsciously a form of appreciation.